The American Association of Public Accountants, Its First Twenty Years / English Accountancy, 1800-1954 (Book). - Littleton, A. C. (The Accounting Review, 1955)
Reviews the books "The American Association of Public Accountants, Its First Twenty Years," compiled by Norman E. Webster and "English Accountancy, 1800-1954," by Nicholas A.H. Stacy.